TEACHING WRITING THROUGH COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) VIEWED FROM STUDENTS’ CREATIVITY - Ani Fiani (LP4MK STKIP PGRI Lubuklinggau, 2013)
This study aims to examine whether: (1) CIRC is more effective than direct instruction to teach writing to the seventh-grade students of MTs N Lubuklinggau in the academic year of 2012/2013; (2) the seventh-grade students who have high creativity have better writing skill than those who have low creativity; (3) there is an interaction between teaching methods and students’ creativity for teaching writing. This research uses a quasi-experimental study, especially a factorial design. The results indicate that: (1) CIRC is more effective than direct instruction to teach writing in the seventh-grade students of MTs N Lubuklinggau in the academic year of 2012/2013; (2) the students having high creativity have better writing skills than the students having low creativity; and (3) there is an interaction between teaching methods (CIRC and Direct Instruction) and the students’ creativity (high and low) for teaching writing. EFL teachers in Indonesia can consider CIRC an alternative way to improve their students' writing ability, mainly writing descriptive texts.